HAK HADHANAH IBU PENDERITA EPILEPSI DAN BIPOLAR DISORDER DALAM HUKUM INDONESIA : Maternal Hadhanah Rights of Mothers Diagnosed with Epilepsy and Bipolar Disorder in Indonesian Law - Safadilla Apsari Mujab; Setyaningsih (Reformasi Hukum Trisakti, 2026)
This study examines the legal status of mothers diagnosed with epilepsy and bipolar disorder as holders of hadhanah (child custody) rights under Indonesian law. The research employs a normative legal method with statutory and conceptual approaches. The findings indicate that the mother’s priority right to custody of children who have not yet reached mumayyiz age, as stipulated in Article 105 of the Compilation of Islamic Law, is not absolute. Pursuant to Article 156(c) of the Compilation of Islamic Law, custody may be transferred if the mother is proven unable to ensure the child’s physical and psychological safety. A diagnosis of epilepsy or bipolar disorder does not automatically invalidate maternal custody rights unless it is demonstrated to pose a tangible risk to the child’s best interests. Accordingly, custody determinations are case-specific and must be grounded in the principle of the best interests of the child.